The prospects of employing probiotics in combating COVID-19 - Moutoshi Chakraborty; Saurab Kishore Munshi (Tzu-Chi Medical Journal, 2022)
Unanticipated pathogenic risk and emerging transmittable diseases can result from interspecies exchanges of viruses among animals and humans. The emergence of the novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) causing coronavirus disease-19 (COVID-19) pandemic has recently exemplified this mechanism. Cough, fever, fatigue, headache, sputum production, hemoptysis, dyspnea, diarrhea, and gastrointestinal disorders are the characteristic features of the disease. The most prevalent and serious manifestation of the infection tends to be pneumonia. The new strains of SARS-CoV-2 with more infectivity have been emerging at regular intervals. There is currently no World Health Organization-approved particular drug for COVID-19. Besides, developing novel antivirals would take much time. Thus, repurposing the application of natural products can provide alternatives and can facilitate medication against COVID-19 as well as can slow down the aggressive progression of the disease before the arrival of approved drugs. Probiotics have long been known for their positive effects on the gut microbiome and impact on immune responses. Particularly, their involvement against viral diseases, especially those of the upper and lower respiratory tract, is of current interest for their prospective application against COVID-19. In this review, we comprehensively address the mode of action of probiotics and their possible intervention against coronavirus diseases correlating with their efficacy against viral diseases. In this regard, we explored recently published relevant research and review articles in MEDLINE/PubMed related to COVID-19 and the effects of probiotics on viral infections.